Comparative morphology of the mandibles and head structures of corbiculate bees (Hymenoptera: Apidae: Apini). (27th October 2015) - PORTO, DIEGO S.; VILHELMSEN, LARS; ALMEIDA, EDUARDO A. B.
Abstract: Phylogenetic relationships of corbiculate bees have been a well‐known focus of controversies over the past 30 years. The majority of the morphological datasets support the monophyly of Apina + Meliponina, whereas molecular datasets recover Meliponina as sister to Bombina. This issue is especially critical to the proper understanding of the evolution of clusters of traits that define the corbiculate eusocial behaviour. This work provides a description and discussion on characters of the head capsule, mandibles and sitophore of bees. Thirty‐three characters are proposed and optimized within concurrent phylogenetic hypotheses for corbiculate bees, which results in seven derived character‐states supporting the monophyly of the Apina + Meliponina + Bombina and nine supporting the Apina + Meliponina clades. Although some striking synapomorphies (e.g. tentorial bridge, pleurostomal condyle, hypopharyngeal lobe) support the former clade, most characters supporting the latter (i.e. Apina + Meliponina) were losses/reductions. Moreover, two previously undescribed character transformations on hypostoma and sitophore favour the Bombina + Meliponina clade. Internal head capsule characters are useful for phylogenetic analysis in comparative studies of bees, and corbiculate bees in particular, when efforts are made to solve the 'corbiculate controversy'. An attempt is made to standardize the current terminology used for bees and for other Hymenoptera.